Diet composition and foraging habitats of Adélie and gentoo penguins in three different stages of their annual cycle - Juares, Mariana Alejandra; Santos, Maria Mercedes; Mennucci, Jorge A.; Coria, Néstor Rubén; Mariano y Jelicich, Rocío (Marine Biology)
We evaluated the diet of Adélie (Pygoscelis adeliae) and gentoo (P. papua) penguins at Stranger Point colony (25 de Mayo/King George Island) during different stages of their annual cycle using the stable isotope method and the conventional dietary analyses (i.e. stomach contents). Antarctic krill (Euphausia superba) dominated the diet of Adélie and gentoo penguins in all three studied stages (pre-breeding, breeding and post-breeding). Nevertheless, only in gentoo penguins a shift in the diet was evident from mainly krill during the breeding stage to mixed diet (i.e. krill and fish/squids) during the pre- and post-breeding stages. Results from stable isotopes suggest that Adélie penguins might be foraging in southern localities compared to their congener during the inter-breeding period. Moreover, Adélie penguins showed a large individual variability in foraging habitat during the post-breeding stage. However, our model has predicted that both species exploited similar areas during the breeding season. The results obtained during the chick-rearing stage were compared with the stomach contents of both species obtained during the same season (2011/2012). Our findings provide new knowledge on the feeding ecology and foraging habitats of pygoscelid penguins. They confirm the importance of Antarctic krill during the annual cycle and improve the understanding of life strategies and predator–prey interactions essentially out of the reproductive period, in which the information is very limited. These results can help to establish new management strategies, particularly considering the potential overlap between predators and fisheries. Fil: Juares, Mariana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Santos, Maria Mercedes. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio ...